PENGEMBANGAN MODUL PEMBELAJARAN FISIKA BERBASIS PENGETAHUAN TEMPATAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA - M.Yasin, Ruhizan (Proceeding 7th International Seminar on Regional Education, 2015)
Abstract This research aims to develop a modul of learning science physic based on local knowledge for junior high school class VIII qualified and student learning outcomes know after a learning process. This study using a method of research and development ( R & D ) with reference to the model 4_D.learning that a device develop in this research about lesson plan, worksheet students ,the assessment of the test resultsand learning. An instrument used is a sheet of validation lesson plans, worksheet and assessment of learning about the rest results. Expended by using trial design pretest â posttest control group. learning outcomes data analyzed by test t. research and development that has been implemented provide a summary : 1. The quality of module of learning developed got value by the category of very good that being used, and 2. The outcomes to study for students after participating in a learning process by the use of module oriented learning the local knowledge had increasing.Keywords: The device of learning, R & D, learning and teaching based on local knowledge, learning outcomes.